Organizational use of social media during a global health crisis - Shi, Wanzhu; Yeung, Tina; Dmello, Jared (Frontiers in Communication, 2024)
account the digital divide among racial/ethnic minorities' access to health information and the higher prevalence of low health and digital literacy among these groups (Goulbourne & Yanovitzky, 2021). According to Ballew, et al.'s study (2020), 39% of African Americans and 30% of Hispanic adults needed more knowledge about the COVID-19 virus compared to Caucasians (22%), so that they can take more protective actions for themselves and their families. Additionally, these population groups also indicated that they relied heavily on social media as a major source of obtaining this information (Ballew, et al., 2020). Although all demographic groups had higher-than-normal increases in deaths during the pandemic, the increase in Hispanic deaths between 2019 and 2020 had a notable surge, compared to other demographic groups (Sabo & Johnson, 2023). As one of the largest minority groups in the U.S.with the second lowest literacy (the first being the Native Hawaiian/Pacific Islander population group), Hispanics may be more susceptible to health misinformation on social media in an English speaking dominated country. Therefore, this study aims to explore how governmental agencies and other health-related organizations use social media within a Hispanic community.In the current digital era, many governmental organizations, non-profit organizations, and hospitals utilize social media, like Twitter (now known as X), to disseminate important public health information. A study showed that most local health departments nationwide have adopted at least one form of social media platform (Harris et al., 2013). Increased connectivity also serves as a mechanism of empowerment, enabling individuals and organizations to interact in new ways for positive change. During the COVID-19 pandemic, governmental agencies, non-profits organizations, and other organizations utilized social media platforms, like Twitter, to disseminate important public health information to their local communities.